Peningkatan Kualitas Kerja, Budaya Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai Dalam Mewujudkan Good Governace Sebagai Variabel Moderasi (Studi Pada Aparatur Sipil Negara Pemerintah Kabupaten Maybrat) - Markus Sory; Muryati; Ana Sopanah; Aji Suraji; Rahayu Puji Suci (Journal of Innovation Research and Knowledge, 2026)
Abstrak: The purpose of this study is to analyze the "Effect of Work Quality Improvement, Work Culture, and Work Discipline on Employee Performance in Realizing Good Governance with Job Satisfaction as a Moderating Variable" (A Study on State Civil Apparatus within the Maybrat Regency Government). This research employs a quantitative approach. The population consists of all 3,754 State Civil Apparatus in Maybrat Regency, Southwest Papua Province. The sample size was determined using the Slovin formula, resulting in 150 respondents, which was rounded to 70 employees. Based on the data and information, the researcher selected the sample using a proportionate stratified random sampling technique. The data analysis technique used is Partial Least Square (PLS), utilizing the SmartPLS version 4 software. The research findings indicate that improved performance appraisal can enhance employee performance. However, stronger Work Quality Improvement does not significantly drive employee performance improvement. Similarly, even though Work Culture and Work Discipline become stronger, they are unable to push for better employee performance. Job Satisfaction cannot moderate the relationship among Work Quality Improvement, Work Culture, and Work Discipline. Furthermore, Work Culture cannot moderate the relationship between Work Discipline and employee performance.